Molecular Docking Approach Of Brewed Coffee Compounds As Neuroprotective Agent - Dewi Ratih Tirto Sari; Reni Ustiatik; Siti Zamilatul Azkiyah (Universitas Islam Negeri Imam Bonjol Padang, 2023)
Coffee is the most popular beverage in the community and the main export commodity in Indonesia. coffee has a special flavor due to roasting and brewing techniques. This study identified the potential neuroprotective effect of eight compounds in brewed coffee through acetylcholinesterase inhibition by molecular docking. Molecular docking approach was conducted in this study. Eight compounds involved 2-Ethyl- 3,5 – dimethylpyrazine, Guaiacol, 2-Isobutyl-3- methoxypyrazine, 2- Methylpropanal, 3-Methyl – 2 – butene – 1 - thiol, 3- Methylbutanal, Furaneol, and 2 – Furfurylthiol were retrieved their structure from PubChem NCBI database and redocked with acetylcholinesterase by Molegro virtual docker version 5.0. then, the docking results were visualized and analyzed by PyMol 2.3 and Discovery Studio version 21.1.1. the docking studies performed that eight brewed coffee compound showed interaction with acetylcholinesterase at the protein gate and active sites. Even the interaction was not found in catalytic triad, the interaction of ligands – protein change the conformation and prevent the breaking down of acetylcholine to acetic acid and choline. This study suggested that eight brewed coffee compounds potentially as neuroprotective effect trough blocking acetylcholinesterase protein.